General versus spinal anaesthesia and postoperative delirium in an orthogeriatric population. (13th September 2015) - Ilango, Sivarajah; Pulle, Ranjeev Chrys; Bell, Jack; Kuys, Suzanne S
Abstract : Aim: Postoperative delirium is common among elderly hip surgery patients. We aimed to pragmatically evaluate whether type of anaesthesia influenced postoperative delirium in an orthogeriatric population following hip fracture. Method: This observational study comprises prospectively collected data on hip fracture patients admitted between October 2010 and November 2011. Delirium was diagnosed clinically by geriatricians. Results: Of the 344 patients admitted, seven managed conservatively and 19 with incomplete data were excluded; 318 patients were analysed. Average age was 81.6 (SD 9.8) years; 28% were men and 167 (53%) were administered general anaesthesia. Mean length of stay was 18 (SD 9.4) days. Overall, 172 patients (54%) experienced delirium. There was no apparent difference in postoperative delirium by anaesthetic type (88 vs 84, P = 0.15). Conclusion: Delirium was common in both general and spinal anaesthetic patients. Further randomised controlled trials would be required to determine whether anaesthesia type influenced delirium rates.